1989
DOI: 10.1203/00006450-198912000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Central Hemodynamic and Regional Blood Flow Changes in the Newborn with Right Ventricular Hypertension

Abstract: ABSTRACT. To evaluate the central hemodynamic and regional blood flow changes associated with right ventricular hypertension in the newborn, 13 anesthetized, mechanically ventilated piglets less than 3 d old were acutely instrumented to permit measurements of central vascular pressures, cardiac output, and regional blood flow (radiolabeled microsphere technique). After initial measurements, right ventricular afterload was progressively increased by means of a pulmonary arterial mechanical occluder until right-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Progressive increase in PVR without a parenchymal lung disease is shown to result in a significant fall in systemic arterial pressure in adults and newborns, apparently through decreased left ventricular output (21,22). Our present and earlier findings however indicate that the vascular hypertensive response in meconium-contaminated newborn lungs is not connected with significant changes in cardiac output or systemic arterial pressure (2,23).…”
Section: Discussioncontrasting
confidence: 47%
“…Progressive increase in PVR without a parenchymal lung disease is shown to result in a significant fall in systemic arterial pressure in adults and newborns, apparently through decreased left ventricular output (21,22). Our present and earlier findings however indicate that the vascular hypertensive response in meconium-contaminated newborn lungs is not connected with significant changes in cardiac output or systemic arterial pressure (2,23).…”
Section: Discussioncontrasting
confidence: 47%
“…Further, an increase in PsA has been shown to lead to an increase in cardiac output in adult animals with RVH (4,5), likely as a result of reestablishment of adequate right ventricular coronary perfusion compromised by the increase in right ventricular intracavitary pressure (4). However, in our newborn pig model of RVH, myocardial blood flow to the right ventricular free wall is actually.increased much above baseline values (2). In addition, although Qp increased along with increasing PsA, and this was associated with a 20% increase in mean right ventricular myocardial blood flow, this increase in coronary blood flow did not achieve statistical significance and changes in myocardial flow did not correlate with changes in Qp.…”
Section: Discussionmentioning
confidence: 64%
“…In the newborn pig, we have previously shown that RVH is associated with a significant decrease in PSA and cardiac output (1,2). The factors responsible for the reduction in cardiac output during RVH are presently unclear, but previously reported data suggest that the reduction is related to the changes in PSA (3-6).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This syndrome is characterized by sustained elevation of PVR (15), causing extrapulmonary right-to-left shunting of blood across the DA and foramen ovale and severe hypoxemia (15). PPHN is also usually associated with low systemic pressure and low cardiac output because of increased right ventricular afterload and myocardial dysfunction (5,6). PPHN contributes to significant morbidity and mortality, indicating a need for further study of its pathogenesis and management (35).…”
mentioning
confidence: 99%